Justice and Peace Education: Models for College and University Faculty - Elavunkal, T (Journal of Dharma, 1989)
David M. Johnson, Justice and Peace Education : Models for College and University Faculty, Orbis Books, New York, 1986. pp. 248. 1 6.95.